2022
DOI: 10.1111/cyt.13108
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumour of the rectum with a novel anaplastic lymphoma kinase fusion diagnosed on cytology: Not just another submucosal gastrointestinal stromal tumour!

Abstract: Inflammatory myofibroblastic tumours (IMT) are spindle cell neoplasms most commonly seen in the lungs, with a wide variety of less common extrapulmonary sites including the mesentery, omentum, and intrabdominal sites. On cytological evaluation, these tumours can be difficult to diagnose, given the morphological mimics of other submucosal spindle cell neoplasms, which may be compounded by the relatively small amount of tissue and the uncommon nature of the diagnosis. Immunohistochemical staining and molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…It consists of N-terminal 4 tandemly repeated RNA recognition motifs, which bind to a 3′ poly adenylate [poly(A)] tail of mRNA, followed by a linker region and a conserved C-terminal MLLE domain. So far, only 2 research groups recently reported PABPC1 as the new fusion pattern for ALK ( PABPC1 :: ALK ) in ALK-positive ALCL and inflammatory myofibroblastic tumor, respectively 14,15 . This translocation t(2;8) in both cases occurred when exon 9 of PABPC1 was juxtaposed to exon 20 of ALK , similar to that identified in this case.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It consists of N-terminal 4 tandemly repeated RNA recognition motifs, which bind to a 3′ poly adenylate [poly(A)] tail of mRNA, followed by a linker region and a conserved C-terminal MLLE domain. So far, only 2 research groups recently reported PABPC1 as the new fusion pattern for ALK ( PABPC1 :: ALK ) in ALK-positive ALCL and inflammatory myofibroblastic tumor, respectively 14,15 . This translocation t(2;8) in both cases occurred when exon 9 of PABPC1 was juxtaposed to exon 20 of ALK , similar to that identified in this case.…”
Section: Discussionsupporting
confidence: 75%
“…So far, only 2 research groups recently reported PABPC1 as the new fusion pattern for ALK (PABPC1::ALK) in ALK-positive ALCL and inflammatory myofibroblastic tumor, respectively. 14,15 This translocation t(2;8) in both cases occurred when exon 9 of PABPC1 was juxtaposed to exon 20 of ALK, similar to that identified in this case. Interestingly, overexpression of PABPC1::ALK in murine Ba/F3 cells conferred cytokine-independent proliferation, analogous to that induced by NPM1::ALK fusion protein.…”
Section: Discussionsupporting
confidence: 69%
“…Nearly half of IMTs exhibit clonal abnormalities, which overexpress ALK, suggesting a neoplastic cause. The ALK positivity was correlated with local recurrence, but not distant metastasis (14)(15)(16). Generally, IMTs can occur anywhere in the body, with the lungs being the most common site of IMT.…”
Section: Introductionmentioning
confidence: 99%